Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s40266-020-00784-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of Antidepressants in Older People during a 10-Year Period: An Observational Study on Prescribed Doses and Serum Levels

Abstract: Background According to previous studies, older patients frequently have serum concentrations of antidepressant medication above the recommended reference range. Objective The aim of this study was to investigate whether prescribed doses of antidepressants and the proportion of individuals with serum concentrations above the recommended reference range in older individuals (≥ 65 years) have changed over a 10-year period in Norway. Methods Serum concentration measurements and prescribed daily doses of antidepre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…SRT might be effective in inhibiting infection of SARS-CoV-2 in the central nervous system, thus preventing potential long-term neuronal damage as well as decreasing COVID-19 mortality. Second, SRT has been confirmed as safe for clinical use in specific subjects, such as older patients ( 61 , 62 ), pregnant women ( 63 ), and patients with cardiovascular complications ( 64 , 65 ), who often have increased risk for SARS-CoV-2 infection and infection-associated morbidity and mortality ( 66 , 67 ). They are also not eligible for vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…SRT might be effective in inhibiting infection of SARS-CoV-2 in the central nervous system, thus preventing potential long-term neuronal damage as well as decreasing COVID-19 mortality. Second, SRT has been confirmed as safe for clinical use in specific subjects, such as older patients ( 61 , 62 ), pregnant women ( 63 ), and patients with cardiovascular complications ( 64 , 65 ), who often have increased risk for SARS-CoV-2 infection and infection-associated morbidity and mortality ( 66 , 67 ). They are also not eligible for vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…In order to gain a deeper understanding of the individual medications that could drive the association signals, we performed explorative analysis on the association of commonly used psychotropic medications (16,43,44) with incident post-COVID dementia. We found that valproic acid and haloperidol had the largest effect sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven percent of Norwegian senior residents are prescribed antidepressant drugs, with citalopram and escitalopram being among the most common substances. Twelve percent of users had serum concentrations of citalopram above the recommended reference range, with increasing risk of adverse effects ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Citalopram and escitalopram are mainly subject to hepatic metabolism by CYP2C19. CYP2C19-mutations that reduce metabolism could therefore explain high serum concentrations ( 26 ) of the mother compound (escitalopram/citalopram) compared to the metabolite demethylcitalopram in some patients. Other metabolites include didemethylcitalopram via CYP2D6 metabolism.…”
Section: Discussionmentioning
confidence: 99%